Co‐expression of glycosylated aquaporin‐1 and transcription factor NFAT5 contributes to aortic stiffness in diabetic and atherosclerosis‐prone mice. Issue 5 (22nd January 2020) - Madonna, Rosalinda; Doria, Vanessa; Görbe, Anikó; Cocco, Nino; Ferdinandy, Péter; Geng, Yong‐Jian; Pierdomenico, Sante Donato; De Caterina, Raffaele
Abstract: Increased stiffness characterizes the early change in the arterial wall with subclinical atherosclerosis. Proteins inducing arterial stiffness in diabetes and hypercholesterolaemia are largely unknown. This study aimed at determining the pattern of protein expression in stiffening aorta of diabetic and hypercholesterolaemic mice. Male Ins 2+/Akita mice were crossbred with ApoE −/− (Ins 2+/Akita : ApoE −/− ) mice. Relative aortic distension (relD) values were determined by ultrasound analysis and arterial stiffness modulators by immunoblotting. Compared with age‐ and sex‐matched C57/BL6 control mice, the aortas of Ins 2+/Akita, ApoE −/− and Ins 2+/Akita :ApoE −/− mice showed increased aortic stiffness. The aortas of Ins 2+/Akita, ApoE −/− and Ins 2+/Akita :ApoE −/− mice showed greater expression of VCAM‐1, collagen type III, NADPH oxidase and iNOS, as well as reduced elastin, with increased collagen type III‐to‐elastin ratio. The aorta of Ins 2+/Akita and Ins 2+/Akita :ApoE −/− mice showed higher expression of eNOS and cytoskeletal remodelling proteins, such as F‐actin and α‐smooth muscle actin, in addition to increased glycosylated aquaporin (AQP)‐1 and transcription factor NFAT5, which control the expression of genes activated by high glucose‐induced hyperosmotic stress. Diabetic and hypercholesterolaemic mice have increased aortic stiffness. The association of AQP1 and NFAT5 co‐expression with aortic stiffness in diabetes and hypercholesterolaemia may represent a novel molecular pathway or therapeutic target.